If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -7x = 34x + 15 Reorder the terms: 9 + -7x = 15 + 34x Solving 9 + -7x = 15 + 34x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-34x' to each side of the equation. 9 + -7x + -34x = 15 + 34x + -34x Combine like terms: -7x + -34x = -41x 9 + -41x = 15 + 34x + -34x Combine like terms: 34x + -34x = 0 9 + -41x = 15 + 0 9 + -41x = 15 Add '-9' to each side of the equation. 9 + -9 + -41x = 15 + -9 Combine like terms: 9 + -9 = 0 0 + -41x = 15 + -9 -41x = 15 + -9 Combine like terms: 15 + -9 = 6 -41x = 6 Divide each side by '-41'. x = -0.1463414634 Simplifying x = -0.1463414634
| x^2+32x+5= | | 25=2m+5 | | 4x+8=-14-7x | | 4w-24=3w+3 | | 6w-4=2(3w+6) | | 16=5x+6 | | 4y-(y-4)=-20 | | 3z-7=11 | | 25x+4=79 | | x+7=2x-5 | | 2x+11=46-3x | | 2x-1= | | 2n+14= | | 4x+3(2x+4)=132 | | -5y+3=8 | | 5x-3=-28 | | 4y-8+6y=12 | | 2r+9=-17 | | 9m+14=12m | | 3x-1=12x-55 | | (x-1)=-4x+29 | | 3x+36=10x-41 | | -2*2+((-1)3-3)2= | | 7.083333333=x^2-3x+6.75 | | 7.5(x-4)=-0.5x+34 | | x^2-(m+3)x+11=0 | | 14-4(3x+1)-8+2x-2= | | 8*14*11= | | 6x+59=12x+11 | | 3x^2-9x+20.25=21.25 | | q+14=8q+56 | | (2x+3)(x-1)=18 |